Ecological Capacity Assessment for Ecotourism Development Using Geographic Information System (Case Study: Mianeh County) - Hojjat Mohamadi Torkamani (تحقیقات کاربردی علوم جغرافیایی)
Ecotourism, as the leading sector of the tourism industry, relies on utilizing environmental capabilities, and needs proper management decisions. In this context, the identification of ecological and environmental power is the most basic step. This study by considering the middle of the city as the sample of this province due to its ecological superiority and using the hierarchical analysis process, attempts to zon the city based on ecological power using the system Geographic Information (GIS). This zoning is done using 11 indicators. The results indicate that about 78 percent of the city's area is in an appropriate and even better condition for the development of ecotourism, and in contrast, about 23 percent of its area faces limitations for the development of ecotourism. In a general conclusion, it can be admitted that the city of Midian has a variety of sub-climates as it covers a wide range, and, in terms of ecotourism potential, there is a significant difference between sectors and regions of existence has it.